Operation Analysis of Soft Switching PWM DC-DC Converter with Secondary Snubber - Dudrik, Jaroslav; Bodor, Marcel; Nistor, Daniel Trip (Communications - Scientific Letters of the University of Zilina, 2013)
The paper deals with analysis of operation of a soft switching PWM DC-DC full-bridge converter with new energy recovery turn-off snubber on secondary side of high frequency power transformer.Principal equations are derived for individual operation states. On the basis of them the diagrams are made out. The diagrams give complex image on the converter behaviour during whole period of operation at nominal load. Theoretical waveforms are compared with simulation results.
Keywords: snubber; soft switching; zero voltage zero current switching; PWM; DC-DC converter